PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING BERBANTUAN MEDIA FILT THE FLAP BOOK TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS IV SDN 76 TAROWANG KEC. GALESONG SELATAN KAB. TAKALAR - Ikhwanul Ikhsan; Aliem Bahri; Anin Asnidar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The main problem in this study is the low learning outcomes of Indonesian language participants taught by the provision of media variations by teachers. The study aims to determine the influence of the Discovery Learning learning model Assisted by Filt The Flap Book media on the learning outcomes of Indonesian language in class IV SDN 76 Tarowang. With the research problem "Is there an influence of the Discovery Learning learning model assisted by Filt The Flap Book media on the learning outcomes of Indonesian language in class IV SDN 76 Tarowang?" The method used in the study is the experimental method in the form of a pretest posttest One group design. The research sample was students of SDN 76 Tarowang Class IV. The total number of questions is 20 questions, multiple choice tests with a total of 20 questions. Data collection techniques use direct observation, tests and documentation. The data analysis technique used in the study is the test data analysis technique / T-test where the data collected will be processed and analyzed using normality tests and hypothesis tests using SPSS version 22. The results of the pretest data study or before using the Discovery Learning learning model assisted by the filt the flap book media are of low quality, namely the average score is 33.07. Meanwhile, the average score of the post-test results after using the Discovery Learning learning model assisted by the filt the flap book media was 83.65 which is quite high. After being analyzed by inferential statistics, the p-value of learning outcomes was obtained, namely 0.000. So 0.000 <0.05 or p-value <0.05. It can be concluded that H1 is accepted and H0 is rejected, meaning that the use of the Discovery Learning learning model assisted by the filt the flap book media has an effect on the learning outcomes of Indonesian language in class IV Sdn 76 Tarowang, South Galesong District, Takalar Regency.